Complexity in Society: From Indicators Construction to their Synthesis - Maggino, Filomena (Springer International Publishing : Imprint: Springer, 2017)
This volume discusses the many recent significant developments, and identifies important problems, in the field of social indicators. In the last ten years the methodology of multivariate analysis and synthetic indicators construction significantly developed. In particular, starting from the classical theory of composite indicators many interesting approaches have been developed to overcome the weaknesses of composites. This volume focuses on these recent developments in synthesizing indicators, and more generally, in quantifying complex phenomena.
Keywords: Social sciences.; Medical research.; Statistics.; Quality of life.; elektronické knihy; electronic books